Web-Based Online Sales Information System Using PHP and MYSQL Database in Nara Collection - Hendriyanto, Hendriyanto; Cakranegara, Pandu Adi (Graduate Program Magister Manajemen Pendidikan, 2022)
Online sales is an alternative form of business that can be used by business people to offer products to consumers. As internet service users continue to grow, due to being cheap and easy, business online sell is growing. Business development is supported by increased productivity which provides a variety of products to be marketed through the internet media. This has triggered the rise of ballet shoes selling business through the internet called